ANALISIS KETERAMPILAN PSIKOMOTORIK DALAM MENGGUNAKAN MIKROSKOP PADA MAHASISWA FARMASI - manalu, Adelya (JIFI (Jurnal Ilmiah Farmasi Imelda), 2021)
This study aims to analyze the psychomotor skills of Pharmacy students in using a microscope. This research is an observational study using a quantitative approach. The population in this study were all active students of Pharmacy of Imelda Medan University. Sampling was done by using simple random sampling technique. Data analysis was carried out by means of descriptive analysis, namely to get an overview of the distribution of research results for each variable categorically with descriptive percentages. The results showed that on average, UIM Pharmacy students were skilled in using a microscope. The highest percentage of the assessed aspects is in the aspect of turning on and off the microscope with a skilled presentation of 64.10%. While the lowest presentation is in the aspect of holding glass objects, with the percentage of unskilled at 25, 64% and less skilled at 28,21%.